Modification of Nafion Membranes by IL-Cation Exchange: Chemical Surface, Electrical and Interfacial Study - V. Romero; M. V. Martínez de Yuso; A. Arango; E. Rodríguez-Castellón; J. Benavente (International Journal of Electrochemistry)
Bulk and surface changes in two proton-exchange membranes (Nafion-112 and Nafion-117) as a result of the incorporation of the IL-cation n-dodecyltriethylammonium (or DTA+) by a proton/cation exchange mechanism after immersion in a DTA+ aqueous solution were analysed by impedance spectroscopy (IS), differential scanning calorimetry (DSC), X-ray photoelectron spectroscopy (XPS), and contact angle measurements performed with dry samples of the original Nafion and Nafion-DTA+-modified membranes. Only slight differences were obtained in the incorporation degree and surface chemical nature depending on the membrane thickness, and DTA+ incorporation modified both the hydrophobic character of the original Nafion membranes and their thermal stability. Electrical characterization of the dry Nafion-112 membrane was performed by impedance spectroscopy while different HCl solutions were used for membrane potential measurements. A study of time evolution of the impedance curves measured in the system “IL aqueous solution/Nafion-112 membrane/IL aqueous solution” was also performed. This study allows us monitoring the electrical changes associated to the IL-cation incorporation in both the membrane and the membrane/IL solution interface, and it provides supplementary information on the characteristic of the Nafion/DTA+ hybrid material. Moreover, the results also show the significant effect of water on the electrical resistance of the Nafion-112/IL-cation-modified membrane.